(Research into Expectations of College Mathematics Instructors) - Nowlan, Robert A. (1994)
Keywords: dept.mat; faculty_collection; sabbatical_report

Finite Mathematics with Applications to the Business and Social Sciences - Gulati, Bodh R. (Kendall/Hunt Pub. Co., 1994)
Keywords: Mathematics; dept.mat; faculty_collection

Film Quotations: 11,000 Lines Spoken on Screen, Arranged by Subject, and Indexed - Nowlan, Robert A. (McFarland, 1994)
Keywords: Motion pictures; Quotations, maxims, etc; dept.mat; faculty_collection

Applications über alles: mathematics for the liberal arts - Aboufadel, Edward F (Primus, 1994)
This paper presents a fresh approach to a general education mathematics course. The basic idea is to turn the customary mathematics class on its head by focusing on applications first, through a reading of articles from magazines and newspapers, and then turning to the technical mathematical details. A description of the topics that were covered in my course, along with references to various publications, is given. A course such as this one is important because it conveys how mathematics is serving the goals of society. © 1994 Taylor and Francis Group, LLC.
Keywords: Applied mathematics; Coding theory; Discrete mathematics; General education courses; Geometry; Mathematics in government; Mathematics in industry; Probability; Statistics; dept.mat